SISTEMA MULTIAGENTES PARA GERENCIAMENTO DE TRÁFEGO URBANO - Silva, Marcos Barros e (2005)
This dissertation is part of TMS project whose objective is the development of a Intelligent Traffic Administration System . TMS has three fundamental functions: (1) Manage the necessary resources to the traffic control; (2) aid in the training of traffic employees; and (3) Accompany the changes of the urban traffic for ends of decision. TMS was conceived to assist the cities that doesn't have systems of traffic control and the others witch has the whole mounted structure with interlinked traffic lights. We show the conception of a system that seeks to assist the needs of traffic administration organs and, at the same time, allow its users to aid in the constant evolution of this management. We will specifically treat an architecture based on agents for our system, the technologies which the system uses and interactions among agents of traffic control. The prototype implemented in this work it allows the automation of the mechanisms of Traffic Administration operation - time of green and red of the traffic lights - turning the changes of semaphored plans the more dynamics as possible.